Aktivitas Ngengat Scirpophaga incertulas di Wilayah Kabupaten Klaten - Mohammad Yunus; Edhi Martono; Arman Wijonarko; RC Hidayat Soesilohadi (Jurnal Perlindungan Tanaman Indonesia, 2011)
The activities of Scirpophaga incertulas adult from Klaten Regency were studied from April to November 2010. The purposes of this study were to observe the activity of moth after adult emergence, their flying activity, and eggs oviposition. Two hundred pupae were collected from the field, then incubated in the laboratory and observed every hour for 72 hours. Flying activity was observed every hour by counting the number of moths that were found in the light traps. This observation was replicated three times during the dark; from 6:00 p.m. to 6:00 a.m. Oviposition activity of moths was observed by infesting twenty females of insect on the rice plants planted in the polybag and covered with plastic sheet. This oviposition activity was also observed every hour during the dark; from 6:00 p.m. to 6:00 a.m. in order to get the number of egg-laying moths. The results showed that the emergence of S. incertulas moth was mainly from 2:00 to 4:00 a.m., the flying activity was detected mostly from 6:00 p.m. to 1:00 a.m., and the moths ovipositing activity was mainly occured from 7:00 to 11:00 p.m. In addition, we found that the intensity of light affected the number of moths coming into the light trap. The light exposed from the 23 Watt lamp (1,500 lumen) was twice more effective in attracting the moths than the 11 Watt lamp (700 lumen).